Pregnancy: A window of opportunity for refining and mitigating the fetal origins of adult health and disease, and maternal cardiovascular futures - Joewono, Hermanto T (Universitas Airlangga, 2025)
HIGHLIGHTS Maternal nutrition, mental health, and environmental factors during pregnancy significantly influence the long-term physical and mental health of offspring, supporting the concept of Fetal Origins of Adult Disease (FOAD) and Developmental Origins of Health and Disease (DOHaD). Adverse pregnancy outcomes like preeclampsia and gestational diabetes increase the mother's future risk of cardiovascular disease, highlighting the need for broader maternal health strategies beyond childbirth. ABSTRACT This review explores the profound impact of pregnancy on fetal development and long-term maternal cardiovascular health, emphasizing how early-life conditions shape lifelong health. The concept of Fetal Origins of Adult Disease (FOAD) or Developmental Origins of Health and Disease (DOHaD) is discussed, highlighting how maternal nutrition and environmental factors during pregnancy predispose offspring to chronic diseases later in life. Maternal mental health is also explored, with depression and anxiety during pregnancy linked to lasting effects on offspring, including increased risks of mental health disorders and chronic conditions in adulthood. The study